The Effect of Combination Therapy of A Warm Ginger Stew Compress and Ki. 3 Point Acupressure on The Pain Level of Gout Arthritis Patients In Indonesia - Enji Meilia Era Pertiwi; Sidik Awaludin; Annas Sumeru (Jurnal Ners, 2019)
Introduction: Gout arthritis is a systemic disease caused by deposition of monosodium urate crystals in the joints,  causing pain. Pain management may include complementary therapy such as combination therapy of a warm ginger stew compress and Ki. 3 point acupressure to reduce pain. This research aimed to examine the effect of combination therapy of a warm ginger stew compress and Ki. 3 point acupressure on the pain level of gout arthritis patients.Methods: The research design for this study is a quasi-experiment pre-test and post-test, with a control group design for 30 respondents. The respondents were assigned to an experimental group with combination therapy of a warm ginger stew compress and Ki. 3 point acupressure for about 30 minutes, and a control group with a warm ginger stew compress for about 15 minutes. Each group consisted of 15 people. The data was analysed using a paired t-test, independent t-test, and Mann Whitney test.Results: The Mann Whitney test showed an average decrease of pain level in the experimental group of 1,7333 and the control group of 1,0667 so, there were differences in the decreased of pain level before and after intervention between the two groups with p-value=0.013.Conclusion: Combination therapy of a warm ginger stew compress and Ki. 3 point acupressure were effective in decreasing the pain level of gout arthritis patients in Puskesmas 1 Purwokerto Timur. This therapy can be used for the gout arthritis patient to reduce pain level.